2020
DOI: 10.1371/journal.pone.0239317
|View full text |Cite
|
Sign up to set email alerts
|

Preocular sensor system for concurrent monitoring of glucose levels and dry eye syndrome using tear fluids

Abstract: The present study demonstrated a noninvasive preocular sensor system for the concurrent monitoring of diabetes and one of its prevalent complications, dry eye syndrome (DES), using tear fluids. Two distinct sensors, i.e., the glucose and DES sensors, were prepared and encased together in a single housing unit to produce the sensor system, and the tip was designed to be in contact with the eye surface noninvasively to collect and deliver tear fluid to the sensors. The glucose sensor was modified from a commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…[ 117 ] Furthermore, a glucose sensor embedded in the contact lens continuously monitors glucose levels for diabetic diagnostics by accessing tears. [ 118 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 117 ] Furthermore, a glucose sensor embedded in the contact lens continuously monitors glucose levels for diabetic diagnostics by accessing tears. [ 118 ]…”
Section: Discussionmentioning
confidence: 99%
“…To measure the volume of the collected tear fluid, a noninvasive preocular contact tip would transfer basal tear fluid into the implanted glucose and DES sensors without harming the ocular tissues. The in vivo experiment demonstrated that the two sensors had acceptable accuracy and high sensitivity, and they might provide an alternative, minimally invasive strategy for the chronic management of diabetes and DES 53 . Moreover, Yetisen et al developed a multiplexed scleral lens sensor consisted of fluorescent probes to measure the pH value and electrolyte (Na + , K + , Ca 2+ , Mg 2+ , and Zn 2+ ions) concentrations in the physiological state.…”
Section: Noninvasive Diagnosis Of Contact Lens—biosensormentioning
confidence: 99%
“…The in vivo experiment demonstrated that the two sensors had acceptable accuracy and high sensitivity, and they might provide an alternative, minimally invasive strategy for the chronic management of diabetes and DES. 53 Moreover, Yetisen et al developed a multiplexed scleral lens sensor consisted of fluorescent probes to measure the pH value and electrolyte (Na + , K + , Ca 2+ , Mg 2+ , and Zn 2+ ions) concentrations in the physiological state. Different probes were used to detect different ions.…”
Section: Multifunctional Smart Contact Lens Sensormentioning
confidence: 99%
“…Tears, also known as lachrymal fluid, are from the secretion of the lachrymal gland covering the eye. Han et al proposed a noninvasive preocular sensor system based on the commercially available electrochemical sensor and dry eye syndrome (a prevalent complication of diabetes) sensor for the continuous monitoring of diabetes and dry eye syndrome [ 93 ]. It could estimate the blood glucose levels by the result acquired from the system with acceptable accuracy that was in validation with that of a clinical glucometer.…”
Section: Smartphone-based Wearable Glucose Monitoringmentioning
confidence: 99%